Office of the Mufti in Malaysia: legal history and constitutional role - Mohd Kamal, Mohd Hisham (LexisNexis, 2009)
This article finds that the office of the State mufti in Malaysia has a long history before the independence of the country. It also examines the constitutional structures within which the office operates. It also opposes the suggestion for the creation of the office of a grand mufti.